Comparison the diagnostic value of serological and molecular methods for screening and detecting Chlamydia trachomatis in semen of infertile men: A cross-sectional study - Amin Khoshakhlagh; Reza Salman Yazdi; Farah taj Navab-Akbar; azadeh ghaheri; shaghayegh sadeghinia; farid dadkhah (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Chlamydia trachomatis (CT) with damaging effects on sperm quality parameters can often cause infertility in men. Objective: The main objective of this study was to determine the diagnostic value of polymerase chain reaction (PCR) and enzyme linked immuno sorbent assay (ELISA) for screening and detecting CT in semen samples of infertile men. Materials and Methods: In this cross-sectional study, 465 men referring to the clinical laboratory of Royan Institute were chosen for primary screening and detection of the presence of CT. 93 samples were normozoospermia with normal sperm parameters i.e. sperm number, motility and morphology (Asymptomatic) and 372 had abnormal sperm parameters (Symptomatic) in semen analysis. ELISA test was performed as the screening test. Samples with optical density (OD) >0.200 were selected as the case and asymptomatic samples with OD <0.200 were selected as the control group for the confirmatory test. PCR assay was used to confirm the serological results. Results: In the case groups (n=62), 4 out of 32 symptomatic samples (12.5%), and 1 out of 30 asymptomatic samples (3.3%) revealed positive results in PCR. No PCR positive sample was observed in the control group (n=34). The final results revealed that considering OD >0.400 as the ELISA positive, the diagnostic value of CT-ELISA positive in symptomatic and asymptomatic infertile patients were 0.019 (7 of 372) and 0.021 (2 of 93), respectively. There was no relationship between the presence of CT infection and different sperm abnormalities. Conclusion: The anti-CT IgA ELISA test may be introduced as an appropriate tool for screening purpose in the seminal plasma to select suspicious samples for PCR confirmatory tests.